Determinantes da prática de “income smoothing” em cias abertas: uma análise de empresas brasileiras e americanas - Ricardo Carvalho da Silva (2020)
This research aimed to verify which factors affect the income smoothing practice of Brazilian and American companies, as well as to analyze the differences and similarities of the determinants of this practice in companies between these markets. To this end, we used a sample of 56 companies comprising the IBRX 100 index listed on B3 in the Brazilian case and 173 companies comprising the S&P 500 index listed on the New York Security Exchange - NYSE. The data selection period was from 2010 to 2018. The Logit model was applied to estimate the probability of incurring the smoothing practice with the use of three metrics indicating smoothing of results. From the results, through the metrics, it was concluded that, on average, 54% of the Brazilian companies listed in the IBRX100 index and 36% of the American companies, listed in the S & P500 index tend to incur the practice of earnings smoothing. It was observed in the studied sample that Brazilian companies were more likely to incur the practice of earnings smoothing. The research allowed us to conclude that the probability of incurring smoothing, to a greater or lesser degree, will be due to the following factors for Brazilian companies, in the case of an increase in this practice, leverage, concentration of ownership as well as the type of majority shareholder and the fact of having shares listed on the New York Stock Exchange, on the other hand, the reduction is caused by the size and sector in which the company operates; due to the fact that it is segmented on B3's Novo Mercado; by hiring one of the Big Four. In the same way in American companies, it was concluded that the determinants of the increase in the smoothing practice were leverage and the sector in which it operates, whereas the reduction was determined by the Beta risk and the rating given in the credit rating and the size from the company. In common, between the two markets, the following factors were verified: the size, the leverage and the sector of activity, in the latter acting in an inverse way as to the increase or reduction. The study contributes to the advancement of research on the practice of smoothing results, presenting what increases or reduces this practice in the Brazilian and American markets, as well as their differences and similarities.